Vitamin D3-loaded electrospun cellulose acetate/polycaprolactone nanofibers: Characterization, in-vitro drug release and cytotoxicity studies - Wsoo, Mohammed Ahmad; Abd Razak, Saiful Izwan; Mohd Bohari, Siti Pauliena; Shahir, Shafinaz; Salihu, Rabiu; Abdul Kadir, Mohammed Rafiq; Mat Nayan, Nadirul Hasraf (Elsevier, 2021)
Vitamin D deficiency is nowa global health problem; despite several drug delivery systems for carrying vitaminD due to low bioavailability and loss bioactivity. Developing a new drug delivery system to deliver vitamin D3 is a strong incentive in the current study. Hence, an implantable drug delivery system (IDDS) was developed from the electrospun cellulose acetate (CA) and ε-polycaprolactone (PCL) nanofibrous membrane, in which the core of implants consists of vitamin D3-loaded CA nanofiber (CAVD) and enclosed in a thin layer of the PCL membrane (CAVD/PCL). CA nanofibrousmat loadedwith vitaminD3 at the concentrations of 6, 12, and 20% (w/w) of vitamin D3 were produced using electrospinning. The smooth and bead-free fibers with diameters ranged from 324 to 428 nm were obtained. The fiber diameters increased with an increase in vitamin D3 content. The controlled drug release profile was observed over 30-days, which fit with the zero-order model (R2 > 0.96) in the first stage. The mechanical properties of IDDS were improved. Young's modulus and tensile strength of CAVD/PCL (dry) were161 ± 14 and 13.07 ± 2.5 MPa, respectively. CA and PCL nanofibers are non-cytotoxic based on the results of the in-vitro cytotoxicity studies. This study can further broaden in-vivo study and provide a reference for developing a new IDDS to carry vitamin D3 in the future.